2016
DOI: 10.1177/0363546516658041
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Year Outcome of a Longitudinal Prospective Evaluation of Isolated Endoscopic Anterior Cruciate Ligament Reconstruction With Patellar Tendon or Hamstring Autograft

Abstract: 4Background: Long-term prospective studies of isolated endoscopic anterior cruciate ligament 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
133
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(155 citation statements)
references
References 54 publications
12
133
1
9
Order By: Relevance
“…Athletes who have had a previous ACLR are at a greater risk of re‐injury, with ACL re‐injury risk ranging from 6% to 26% on the operated limb (graft rupture) and from 2% to 20.5% on the contralateral limb, depending on the follow‐up time scale . Many studies have evaluated the difference in ACL re‐injury rates between BPTB and HT grafts . Thompson et al prospectively studied 180 ACLR athletes with a 20‐year follow‐up and found a significantly greater contralateral ACL injury rate in BPTB (30%) than HT (14%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Athletes who have had a previous ACLR are at a greater risk of re‐injury, with ACL re‐injury risk ranging from 6% to 26% on the operated limb (graft rupture) and from 2% to 20.5% on the contralateral limb, depending on the follow‐up time scale . Many studies have evaluated the difference in ACL re‐injury rates between BPTB and HT grafts . Thompson et al prospectively studied 180 ACLR athletes with a 20‐year follow‐up and found a significantly greater contralateral ACL injury rate in BPTB (30%) than HT (14%).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Many studies have evaluated the difference in ACL re-injury rates between BPTB and HT grafts. 4,6,7 Thompson et al 7 prospectively studied 180 ACLR athletes with a 20-year follow-up and found a significantly greater contralateral ACL injury rate in BPTB (30%) than HT (14%). Other studies have reported similar findings, 4 although differentiation of re-injury rate is not always evident when the sample size is low.…”
Section: Introductionmentioning
confidence: 99%
“…Методика восстановления ПКС постоянно совершенствуется. Опубликовано множество работ, где представлены положительные результаты по улучшению позиции трансплантата и более прочной его фиксации [1,[3][4][5][6][7][8][9]. Появились новые, более щадящие способы с ретроградным сверлением [2,5,10].…”
Section: Introductionunclassified
“…[8][9][10][11] Despite, these results have been controversial and have not been reproduced in other studies. [12][13][14][15][16][17][18][19][20][21][22] There is a lack of conclusive studies in the existing literature regarding the outcomes of ACL reconstructions in females following the various graft types, though these studies could potentially aid in the choice of graft for female patients undergoing ACL reconstruction.…”
mentioning
confidence: 99%